2022
DOI: 10.1088/2043-6262/ac5dc5
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of cerium oxide nanoparticles from turmeric and kinds of honey: characterisations, antioxidant and photocatalytic dye degradation activities

Abstract: The environmentally compatible and cost-effective green synthesis of cerium oxide nanoparticles (CeO2-NPs) was performed starting from bioactive natural materials, i.e., blossom, pine, chestnut honey, and turmeric extracts. The sizes, surface charges, morphologies, band gap energies, antioxidant, and photocatalytic activities of the synthesised nanoparticles were examined comparatively. The x-ray diffraction (XRD) studies confirmed the crystallinity and purity of CeO2-NPs. Transmission electron microscope (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Literature has reported various data where the antioxidant potential of MONPs has been assessed to estimate the overall antioxidant efficacy of these NPs. For instance, iron oxide NPs greenly produced from Camellia sinensis (Paulpandian et al 2022 ), Achillea nobilis (Sepasgozar et al 2022 ), ginger ( Zingiber officinale ), and cumin seeds ( Cuminum cyminum L.) (Noor et al 2022 ); ZnO NPs from Thymbra spicata L. (Gur et al 2022 ), Caesalpinia crista (Donga and Chanda 2022 ), Cladosporium tenuissimum (Mani et al 2022 ), Cystoseira crinite (Elrefaey et al 2022 ); and CeO 2 NPs from turmeric (Kalaycıoğlu et al 2022 ), Spirulina platensis microalgae (Khaligh and Asoodeh 2022 ), etc., exhibited significant antioxidant potential. Herein, we briefly discuss the antioxidant activities of CuO NPs.…”
Section: Antimicrobial Activities Of Metal Oxide Npsmentioning
confidence: 99%
“…Literature has reported various data where the antioxidant potential of MONPs has been assessed to estimate the overall antioxidant efficacy of these NPs. For instance, iron oxide NPs greenly produced from Camellia sinensis (Paulpandian et al 2022 ), Achillea nobilis (Sepasgozar et al 2022 ), ginger ( Zingiber officinale ), and cumin seeds ( Cuminum cyminum L.) (Noor et al 2022 ); ZnO NPs from Thymbra spicata L. (Gur et al 2022 ), Caesalpinia crista (Donga and Chanda 2022 ), Cladosporium tenuissimum (Mani et al 2022 ), Cystoseira crinite (Elrefaey et al 2022 ); and CeO 2 NPs from turmeric (Kalaycıoğlu et al 2022 ), Spirulina platensis microalgae (Khaligh and Asoodeh 2022 ), etc., exhibited significant antioxidant potential. Herein, we briefly discuss the antioxidant activities of CuO NPs.…”
Section: Antimicrobial Activities Of Metal Oxide Npsmentioning
confidence: 99%
“…According to the DPPH technique, all green-synthesized nanoparticles had strong antioxidant activity, with IC50 values ranging from 32.4 to 64.5 μg/ml. Under UV light irradiation, high degradation efficiencies (between 83.9 and 93.4%) for methylene blue dye were achieved due to the CeO 2 NPs' strong redox property [179].…”
Section: Cerium Oxide Nanoparticles (Ceo 2 Npsmentioning
confidence: 99%
“…25,26 The effective use of CeO 2 -NPs obtained by the green method in dye photodegradation has been lately demonstrated. 26 In this study, a polyacrylamide (PAM) hydrogel was chosen among the hydrogels because of its synthetic nature with high water uptake capacity and hydrophilicity. PAM forms a soft gel when hydrated.…”
Section: Introductionmentioning
confidence: 99%
“… 22 24 In addition, it has been shown that CeO 2 nanoparticles synthesized by the green method gain additional and different surface properties. 25 , 26 The effective use of CeO 2 -NPs obtained by the green method in dye photodegradation has been lately demonstrated. 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation